A Systematic Review of the Literature on Maker Education and Teacher Training - Amaia Quintana-Ordorika; Urtza Garay-Ruiz; Javier Portillo-Berasaluce (Education Sciences)
This systematic review aims to analyse the existing research on the introduction of maker education in teacher training and continuous professional development. There is a growing interest in defining the state of the art on this topic. Using the WOS database, 20 empirical studies published in peer-reviewed journals between 2019 and 2023 were further analysed. The studies were systematically examined to identify the general characteristics related to the type of maker education training intervention. The principal findings of this review indicate that the majority of training programmes are primarily aimed at pre-service and in-service teachers, and the number of articles published has increased significantly in recent years; moreover, the characteristics of these programmes vary considerably across the studies identified, indicating an uneven distribution of research activity. Despite the growth in the literature, there is still a notable gap in terms of the specific knowledge acquisition that teachers require in order to effectively implement maker education. While many studies emphasise equipping educators with both practical skills and theoretical knowledge, fewer focus solely on knowledge acquisition. This review emphasises the value of immersive experiences for training teachers, demonstrating the positive impact such experiences can have on their confidence and mindset. Additionally, the potential of virtual training programmes to create collaborative, supportive learning environments represents an innovative approach to enhancing teacher preparation in maker education. Based on the findings, it must be emphasised that there is still a need for the further research and development of maker education training models specifically designed to facilitate the integration of making approaches into formal education.